Ethical considerations in the care of people with eating, drinking and swallowing difficulties. Issue 3 (June 2022) - Leslie, Paula; Lisiecka, Dominika
Abstract : Purpose of review: Eating, drinking and swallowing difficulties are low on the list of clinical headlines. Until something affects the process and then we see how pervasive and devastating such issues are. Recent guidelines have been published looking at national competencies to be structured into preregistration education. Professional bodies have addressed the topic from a risk perspective, which may be counter to the patient-centred approach of shared decision making. Our review places the literature in the wider, historical context of bioethics and our experience regarding ethical challenges as we strive to support our patients. Recent findings: Recent literature addressing ethical care for a person with eating, drinking and swallowing difficulties, highlights shared decision-making. This is guided by patient preference, professional roles and approaches, cultural context and informed consent. Studies highlight the importance of appropriate communication and documentation, and ethical decision-making steps. Summary: We hope to widen clinicians' perspectives and reflection on factors influencing these challenges (including own biases), and how to address them so that the patient and the clinician are satisfied. Ethical approaches require skills and knowledge, and critically also time. Resources should be allocated at the service level to ensure a robust process of informed consent and decision making.